2020
DOI: 10.1176/appi.ajp.2020.19090923
|View full text |Cite
|
Sign up to set email alerts
|

From Rare Copy Number Variants to Biological Processes in ADHD

Abstract: Attention deficit hyperactivity disorder (ADHD) is a highly heritable psychiatric disorder. The objective of this study was to define ADHD-associated candidate genes and their associated molecular modules and biological themes, based on the analysis of rare genetic variants. Methods:The authors combined data from 11 published copy number variation studies in 6,176 individuals with ADHD and 25,026 control subjects and prioritized genes by applying an integrative strategy based on criteria including recurrence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 86 publications
1
25
0
1
Order By: Relevance
“…In a large meta-analysis of seven genome-wide linkage scans in search of loci associated with ADHD, it was determined that the chr16q23.1-qter region, precisely the genomic region containing WWOX, had a very highly significant risk association with ADHD [48]. Furthermore, Harich et al, using data from CNV studies from 6176 ADHD individuals and using multiple additional bioinformatic approaches, identified WWOX as one of a relatively small set of 26 candidate ADHD genes [49]. Distribution of WWOX locus CNVs associated with ASD and ID cases obtained from the AutDB database (http://www.mindspec.org/autdb.html).…”
Section: Figure 8 Wwox Germline Copy Number Variants (Cnvs) In Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…In a large meta-analysis of seven genome-wide linkage scans in search of loci associated with ADHD, it was determined that the chr16q23.1-qter region, precisely the genomic region containing WWOX, had a very highly significant risk association with ADHD [48]. Furthermore, Harich et al, using data from CNV studies from 6176 ADHD individuals and using multiple additional bioinformatic approaches, identified WWOX as one of a relatively small set of 26 candidate ADHD genes [49]. Distribution of WWOX locus CNVs associated with ASD and ID cases obtained from the AutDB database (http://www.mindspec.org/autdb.html).…”
Section: Figure 8 Wwox Germline Copy Number Variants (Cnvs) In Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…A recent genome-wide meta-analyses identified shared risk loci for ADHD and intelligence [31]. Rare genetic variants have also been identified for cognition [75,76] and ADHD [77], with overlapping genes implicated in ADHD studies of common and rare variants [78]. However, while there is evidence of common and rare variants disrupting similar biological pathways in ADHD [79], the neurobiological mechanisms underlying shared genetic influences on ADHD and intelligence remain unclear [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parent-offspring trio studies of de novo CNVs and SNVs will contribute in disease etiology, since de novo aberrations in genome are more likely deleterious [28]. Identification of disease-associated genes and knowledge of their molecular functions will lead to better understanding of their disease pathology and hopefully enable better diagnostic and treatment [47].…”
Section: Discussionmentioning
confidence: 99%
“…In study of Thapar et al found CNVs in ADHD patients were enriched in genes for which it was previously known to be involved in SCZ, Fragile X ID, and partly with autism [50]. More recently 26 ADHD-associated candidate genes were identified that share common biological topic such as transcription, mitochondrial biology, mRNA metabolism, and cytoskeleton [47].…”
Section: The Importance Of Cnv In Diagnostics Of Adhdmentioning
confidence: 99%
See 1 more Smart Citation